Penerapan Akad Murabahah untuk Pembiayaan Renovasi Rumah pada Kantor Kas PT BPRS Amanah Bangsa Sidamanik - Putri Shakinah; Ahmad Perdana Indra (Universitas Muhammadiyah Enrekang, 2022)
Thisostudyofocuses on theoapplication ofomurabahahocontracts to finance home renovations at the PT BPRS Amanah Bangsa sidamanik cash office. The purposeoof this studyois to find out how the implementation of the Murabahah contract for financingohome renovations and to find out what are the benefits of implementing the Murabahah contract for financing home renovations to customers. The research method used is a library studio by collecting data and utilizing theories related to the problems to be discussed, which are produced from various books related to the study. And also field studies by conducting questions and answers to parties related to this research. The results show that 1) Banks are sellers of raw materials for home renovations and customers are buyers. The bank provides the materials desired by the customer by buying the raw material from the seller/supplier, then selling it to the buyer (customer) at a price different or higher than the purchase price made by Islamic banks 2) There are benefits when using a Murabahah contract in renovation house, namely: avoiding usury, and installment payments are automatically deducted via debit accoun